Newly developed aircraft routing options for air traffic simulation in the chemistry–climate model EMAC 2.53: AirTraf 2.0 - Yamashita, Hiroshi; Yin, Feijia; Grewe, Volker; Jöckel, Patrick; Matthes, Sigrun; Kern, Bastian; Dahlmann, Katrin; Frömming, Christine (Geoscientific Model Development, 2020)
Aviation contributes to climate change, and the climate impact of aviation is expected to increase further. Adaptations of aircraft routings in order to reduce the climate impact are an important climate change mitigation measure. The air traffic simulator AirTraf, as a submodel of the European Center HAMburg general circulation model (ECHAM) and Modular Earth Submodel System (MESSy) Atmospheric Chemistry (EMAC) model, enables the evaluation of such measures. For the first version of the submodel AirTraf, we concentrated on the general setup of the model, including departure and arrival, performance and emissions, and technical aspects such as the parallelization of the aircraft trajectory calculation with only a limited set of optimization possibilities (time and distance). Here, in the second version of AirTraf, we focus on enlarging the objective functions by seven new options to enable assessing operational improvements in many more aspects including economic costs, contrail occurrence, and climate impact. We verify that the AirTraf setup, e.g., in terms of number and choice of design variables for the genetic algorithm, allows us to find solutions even with highly structured fields such as contrail occurrence. This is shown by example simulations of the new routing options, including around 100 North Atlantic flights of an Airbus A330 aircraft for a typical winter day. The results clearly show that AirTraf 2.0 can find the different families of optimum flight trajectories (three-dimensional) for specific routing options; those trajectories minimize the corresponding objective functions successfully. The minimum cost option lies between the minimum time and the minimum fuel options. Thus, aircraft operating costs are minimized by taking the best compromise between flight time and fuel use. The aircraft routings for contrail avoidance and minimum climate impact reduce the potential climate impact which is estimated by using algorithmic climate change functions, whereas these two routings increase the aircraft operating costs. A trade-off between the aircraft operating costs and the climate impact is confirmed. The simulation results are compared with literature data, and the consistency of the submodel AirTraf 2.0 is verified.